The potential of organomineral amendments in increasing the adsorption of lead (Pb) and cadmium (Cd) in a sandy loam soil - M Ghufron Chakim; Wanti Mindari; Bakti Wisnu Widjajani (Brawijaya University, 2022)
Sandy loam soils contain low organic carbon and have low ion adsorption capacity. Under certain conditions, the soils contain heavy metals that are harmful to plants. Soil amendments such as biosilica and humic acid from natural sources are expected to increase the soil adsorption capacity to heavy metals. A simulation experiment consisting of two factors was conducted to explore the effectiveness of humic and biosilica, as soil amendments, in adsorbing heavy metals from soils. The first factor was biosilica dose composing 0 t ha-1 (S0), 0.5 t ha-1 (S1), 1 t ha-1 (S2), and 1.5 t ha-1 (S3). The second factor was the humic acid dose composing 0 kg ha-1 (H0), 20 kg ha-1 (H1), 40 kg ha-1 (H2), and 60 kg ha-1 (H3). The humic acid and biosilica were applied to soil contaminated with Pb and Cd. The results showed that the combination of 0.5 t biosilica ha-1 (S1) and 20 kg humic acid ha-1 (H1) significantly increased soil pH, organic C content, cation exchange capacity, and reduced the availability of Pb and Cd at 90 days after treatment. The Pb and Cd contents in plant tissue decreased from roots to grains. Humic acid treatment was more effective in absorbing Pb of 86.89-90.49% and Cd of 71.47-76.33% than other treatments.